PD0166285 sensitizes esophageal squamous cell carcinoma to radiotherapy by dual inhibition of WEE1 and PKMYT1 - Zhang, Qingyi; Lin, Xu; Jiang, Kan; Deng, Jun; Ke, Lei; Wu, Ziheng; Xia, Pinghui; Li, Qi; Yu, Li; Ni, Pengzhi; Lv, Wang; Hu, Jian (Frontiers in Oncology, 2022)
Background: Esophageal squamous cell carcinoma (ESCC) is an aggressive tumor with a 5-year survival rate of only 20%. More than 80% of ESCC patients possess TP53 mutation, which abolishes the G1/S checkpoint and accelerates the cell cycle. Thus, WEE1 and PKMYT1, regulators of G2/M phase in cell cycle, play essential roles in TP53-mutated cancer cells. PD0166285(PD) is a pyridopyrimidine compound that can inhibit WEE1 and PKMYT1 simultaneously, however, the effects of PD on ESCC, either as monotherapy or in combination therapy with radiotherapy, remain unclear. Methods: To measure the anti-tumor efficacy of PD in ESCC cells, cell viability, cell cycle and cell apoptosis assays were examined in KYSE150 and TE1 cells with PD treatment. The combination therapy of PD and irradiation was also performed in ESCC cells to find whether PD can sensitize ESCC cells to irradiation. Vivo assays were also performed to investigate the efficacy of PD. Results: We found that the IC50 values of PD among ESCC cells ranged from 234 to 694 nM, PD can regulate cell cycle and induce cell apoptosis in ESCC cells in a dose-dependent manner. When combined with irradiation, PD sensitized ESCC cells to irradiation by abolishing G2/M phase arrest, inducing a high ratio of mitosis catastrophe, eventually leading to cell death. We also demonstrated that PD can attenuate DNA damage repair by inhibiting Rad51, further research also found the interaction of WEE1 and Rad51. In vivo assays, PD inhibited the tumor growth in mice, combination therapy showed better therapeutic efficacy. Conclusion: PD0166285 can exert antitumor effect by inhibiting the function of WEE1 and PKMYT1 in ESCC cells, and also sensitize ESCC cells to irradiation not only by abolishing G2/M arrest but attenuating DNA repair directly. We believe PD0166285 can be a potent treatment option for ESCC in the future.